Diagnostico de control quimico de togasodes orisiculus muir en oryza sativa l. variedad ir - 43 en limoncarro, Guadalupe - La Libertad - Ospino Castañeda, Edwar Absalon (2016)
In this research, the visit to 8 rice farmers was conducted, in which we proceeded to conduct the surveys of 2014 and 2015 corresponding campaign, complemented by shooting. In surveys questions that facilitates the diagnosis of chemical control of Togasodes orisiculus Muir in Oryza sativa L. variety IR 43- Limoncarro- performed Guadalupe - La Libertad order to diagnose the chemical control of Togasodes orisiculus Muir in Oryza sativa L . Limoncarro variety IR43, Guadalupe -The Freedom. From the results it was found that farmers in the area of 80% Limoncarro know the problem of insect pest and its damage; and chemical control l Togasodes do orisiculus Muir based active ingredients such as Clothianidin, Thiamethoxam and Imidacloprid. Also, farmers during 2014 and 2015 campaign increased the rate of application is also reflected in an increase of 15% of the cost of production.